Six billion and counting: population growth and food security in the 21st century - Leisinger, Klaus M.; Schmitt, Karin M.; Pandya-Lorch, Rajul (International Food Policy Research Institute, 2002)
In 1999 global population surpassed 6 billion people, and this number rises by about 70-80 million people each year. "Six Billion and Counting" examines the consequences of continuing population growth for the world's resource systems and for national and global food security. Leisinger, Schmitt, and Pandya-Lorch offer here a sober analysis of a complex and alarming situation. They assess the progress the world has made in controlling population growth and point to the areas where future difficulties will lie. They describe the effects of rapid population growth on social and economic conditions and on natural resources, and they consider what population growth will mean for the food security of poor people and poor countries. In addition, the authors make clear how the roles of women and children in traditional societies affect birth rates. "Six Billion and Counting" shows that neither the population pessimists, who predict a catastrophic exhaustion of natural resources, nor the population optimists, who foresee technological solutions for all of the problems raised by population growth, offer the most useful approach to this problem. Instead, Leisinger and his coauthors argue that new technologies mitigating the harmful effects of rapid population growth can give the world valuable time to take the complex and multifaceted steps needed to reduce population growth rates to sustainable levels.